1992
DOI: 10.2165/00007256-199213060-00002
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of Sprint Running

Abstract: Understanding of biomechanical factors in sprint running is useful because of their critical value to performance. Some variables measured in distance running are also important in sprint running. Significant factors include: reaction time, technique, electromyographic (EMG) activity, force production, neural factors and muscle structure. Although various methodologies have been used, results are clear and conclusions can be made. The reaction time of good athletes is short, but it does not correlate with perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
434
3
40

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 522 publications
(504 citation statements)
references
References 40 publications
27
434
3
40
Order By: Relevance
“…There are studies indicating that sprint athletes with higher performance levels are able to generate higher propulsive forces onto the starting blocks (8,16,31,44). Mero et al (32) showed that maximal rate of force development (highest force generated within the smallest time frame) was crucial in attaining maximal block velocity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are studies indicating that sprint athletes with higher performance levels are able to generate higher propulsive forces onto the starting blocks (8,16,31,44). Mero et al (32) showed that maximal rate of force development (highest force generated within the smallest time frame) was crucial in attaining maximal block velocity.…”
Section: Discussionmentioning
confidence: 99%
“…Step frequency depends on the genetic make-up the sprint athlete and the function of the central nervous system that allows greater number of muscle fibers to be recruited (31). As the step frequency increases, step length gets shorter and vice versa is true.…”
Section: Factors Affecting Sprint Start Performancementioning
confidence: 99%
“…However, these scenarios are difficult to standardize and varying skill levels between participants might blur a shoe effect. In addition, the generalizability of this study's findings to the maximum velocity phase of a sprint might be limited as it considerably differs from the early acceleration phase with respect to force and kinematic patterns [34]. Finally, due to the weight bag located at the rear part of the shoes, the weight distribution of the test shoes did not perfectly represent the weight distribution of basketball shoes available on the market.…”
Section: Limitationsmentioning
confidence: 73%
“…A decrease in horizontal breaking force after ground contact has traditionally been suggested to improve sprint start performance [20,34]. Furthermore, increased knee flexion and hip extension, representing a more "active touchdown", might reduce horizontal breaking forces [20].…”
Section: Biomechanicsmentioning
confidence: 99%
“…Sprinting consists of three different phases: initial acceleration, attainment of maximal velocity, and maintenance of maximal velocity 9) . However, sprinters do not acknowledge these components while sprinting because their goals are to reduce sprinting time and to reach the goal line fi rst 2) .…”
Section: Introductionmentioning
confidence: 99%